The right to adequate housing in International Human Rights Law: Polish transformation experiences - Terminski, Bogumil (2011)
AbstractHousing rights are now one of the most fundamental social and economic human rights. It is therefore the duty of every country to implement such rights for its own citizens, irrespective of its economicdevelopment, political situation, or social conditions. Possession of appropriate living conditions determines, in fact, the possibility of using other, more advanced human rights (e.g. the right to health, right to development, right to peace, or access to culture). Realization of the right to adequate housing is increasingly problematic for developed countries. According to the United Nations, there areover 100 million homeless people worldwide and more than 1 billion inadequately housed. Poland is an example of a country particularly afflicted by housing problems after the Second World War.Experiences of Polish democratic transformation after 1989, therefore, provide interesting lessons (and warnings) for all countries wishing to deal with the social problems arising from housing difficulties.Keywords: right to adequate housing, human rights, housing rights, social transformation, transition, economic and social human rights, social issues, Poland, United Nations, communism.ResumenEl derecho a la vivienda es uno de los derechos humanos sociales y económicos más elementales. Por lo tanto, es un deber de todos los países implementar esos derechos para susciudadanos y ciudadanas, independependientmente de su desarrollo económico, situación política, o condiciones sociales. La posesión de adecuadas condiciones de vida determinala posibilidad de utilizar otros derechos humanos más avanzados (por ejemplo, derecho a la salud, derecho al desarrollo, derecho a la paz, acceso a la cultura). La realizacióndel derecho a una vivienda adecuada es cada vez más problemática para los países desarrollados. Según las Naciones Unidas, hay más de 100 millones de personas sin hogar en todo el mundo y más de 1000 millones alojadas en viviendas inadecuadas. Polonia es ejemplo de un país particularmente afectado por los problemas de vivienda después de la Segunda Guerra Mundial. Experiencias de la transformación democrática de Polonia después de 1989 ofrecen lecciones interesantes (y advertencias) para todos los países que deseen hacer frente a los problemas sociales derivados de las dificultades de vivienda.Palabras clave: derecho a la vivienda, derechos humanos, transformación social, transición, derechos económicos y sociales, cuestiones sociales, Polonia, Naciones Unidas, comunismo.